Peningkatan Keterampilan Pra-Membaca Anak-Anak Melalui Penggunaan Limbah Rumah Tangga - Yeni, Elva; Hazizah, Nur (Penerbit Aksara Rentaka Siar (ARS), 2020)
Language is a stage of children’s development which is expreased through thinking using word that mark the increased ability of creativity in accordance with the stage of development. The purpose of this research is to improve children’s pre-reading skills throught the use of household waste (packs/packages) in group A primagama padang kindergarten. This type of research is classroom action techniques are through observation while the analysis technique used is percentage. The results of research in primagama padang creative kindergartens that the child’s ability to increase from each meeting, can be seen from the average in the first cycle 42,19% increased in the second cycle to 84,37% by applying the packaging media in children’s reading ability